If the above integral can be expressed as for positive integers , find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
∫ 0 π / 2 ln ( cos ( x ) ) d x = I = ∫ 0 π / 2 ln ( sin ( x ) ) d x .
By symmetry we have ln ( cos ( x ) ) = ln ( sin ( x ) ) in [ 0 , π / 2 ] ,Thus we have:
2 I = ∫ 0 π / 2 ln ( cos ( x ) ) d x + ∫ 0 π / 2 ln ( sin ( x ) ) d x = ∫ 0 π / 2 ln ( sin ( x ) cos ( x ) ) d x = ∫ 0 π / 2 ln ( 2 1 ⋅ sin ( 2 x ) ) d x .
( I used ln ( a ⋅ b ) = ln ( a ) + ln ( b ) )
Now we split the integral back up to obtain
− ∫ 0 π / 2 ln ( 2 ) d x + ∫ 0 π / 2 ln ( sin ( 2 x ) ) d x = 2 I .
Thus we can now substitute u = 2 x to obtain
− 2 π ln ( 2 ) + 2 1 ∫ 0 π ln ( sin ( u ) ) d u = 2 I
But the integral of ln ( sin ( u ) ) is 2 I , thus we have
− 2 π ln ( 2 ) + I = 2 I , → I = − 2 π ln ( 2 ) .